1994
DOI: 10.2307/3578800
|View full text |Cite|
|
Sign up to set email alerts
|

Age and Radiation Sensitivity of Rat Mammary Clonogenic Cells

Abstract: The relative risk of breast cancer is very high among women who were exposed to ionizing radiation during or before puberty. In the current studies, the surviving fractions of clonogenic mammary cells of groups of virgin rats were estimated after single exposures to 137Cs gamma rays at intervals from 1 to 12 weeks after birth. The radiosensitivity of clonogens from prepubertal rats was high and changed with the onset of puberty at between 4 and 6 weeks of age. By this time, the increase in the size of the clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Clonogenicity of mammary epithelial cells in culture is highly species- and assay-dependent, and difficult to extrapolate between mouse, rat and human. However, a previous study of rat mammary epithelial cell populations suggested that clonogens were only radiosensitive in pre-pubertal development (a result that would correspond to the one reported here) [37], and also showed that the response of clonogenic cells was different for mutagens that did not induce double strand breaks [38].…”
Section: Discussionsupporting
confidence: 84%
“…Clonogenicity of mammary epithelial cells in culture is highly species- and assay-dependent, and difficult to extrapolate between mouse, rat and human. However, a previous study of rat mammary epithelial cell populations suggested that clonogens were only radiosensitive in pre-pubertal development (a result that would correspond to the one reported here) [37], and also showed that the response of clonogenic cells was different for mutagens that did not induce double strand breaks [38].…”
Section: Discussionsupporting
confidence: 84%
“…Stem and progenitor cells constitute a small undifferentiated subpopulation of breast tissue and are the proposed cells of origin of breast cancer [47]. These cells are initially quiescent but begin to proliferate during and after puberty [48]. They have a basal‐like phenotype, and because they lack ovarian hormone receptors they depend on ErbB signaling, probably via the paracrine action of estrogen‐induced amphiregulin [47].…”
Section: Discussionmentioning
confidence: 99%
“…Shimada and colleagues [72] proposed that prepubertal rats are more sensitive to radiation-associated cell killing than older animals because of a relative lack of DNA repair before puberty. In contrast, one of the only studies that included rats (Sprague–Daley) exposed before puberty showed less adenocarcinoma than those exposed at later ages (42–225 days) [73].…”
Section: Modification Of Dose Responsementioning
confidence: 99%